Medidas de engenharia de tráfego para melhorar o acesso ao portão 1 do Campus Universitários do Guamá - AMORAS JUNIOR, Antonio Carlos Monteiro (2025)
Traffic engineering is essential for any city that wants to maintain good traffic flow on its access roads, as its focus is on planning, organizing and managing the flow of vehicles and pedestrians in a safe and efficient manner. However, there are many problems to be solved in the city of Belém, such as access to Gate 1 of the Guamá University Campus. Therefore, the general objective of the study is to propose traffic engineering measures to improve flow and safety at the intersection of Avenida Bernardo Sayão and Rua Augusto Corrêa, through physical separation of traffic directions and the installation of a return device, such as a roundabout, on Rua Augusto Corrêa. This proposal seeks to reduce the points of traffic conflict, ensure the implementation of appropriate signage and, in addition, the study considers the impact of Traffic Generating Hubs (PGTs) on the site, since these areas increase the volume of vehicles and influence the safety and quality of traffic in the surrounding area. To do this, the following methods were used: traffic counting; vehicle classification through image recording; and evaluation of the intervention geometry. This stage took place during the three main peak hours of a regular academic day at UFPA, lasting one hour in each period. The data indicated that the proposed physical separation and roundabout would reduce conflict points, with the road geometry accommodating critical vehicles.. The analysis showed that these interventions would meet safety demands and improve mobility, benefiting the safety of both pedestrians and drivers. It is concluded that the suggested interventions are effective and potentially advantageous for traffic organization and safety in the studied area, demonstrating that the proposals contribute to more efficient and safer traffic management.